The Quality of e-Village Budgeting Service : An Empirical Research in Banyuwangi, Indonesia - Beny Prasetyo; Syaiful Bukhari; Dwiky Bagas Regio Perkasa (IAES Indonesia Section, 2019)
Electronic Village Budgeting (e-VB) is an information system of village budgeting owned by Banyuwangi District. But at the beginning of the implementation of e-VB, there were several errors and constraints experienced by users so that an evaluation is needed to measure the extent of the quality of e-VB services. To measure the quality of e-VB service, this research used 33 attributes from 6 dimensions of e-GovQual; ease of use, trust, functionality of the interaction environment, reliability, content and performance of information, and citizen support. While the Importance Performance Analysis (IPA) method is used to map the services performance based on the level of user importance. Respondents in this research were 44 respondents spread across 22 villages in Kabat and Licin subDistricts. Based on the results of e-GovQual analysis was known that the quality of service performance is 3.16. This shows that the performance of the e-VB service is good according to the user's perception. However, based on the assessment of user importance of 3.45, it creates a gap value between performance and importance of -0.29, indicating that the quality of e-VB services is good, but has not fulfilled the user’s importance. Based on the results of the IPA quadrant analysis, it produces several attributes that need a special priority for improvement; providing informed consent, accessibility of site, and loading speed. The results of the research are expected to help the provider of e-VB to be able to provide services that are in accordance with the user’s importance.